Processo decisório de policiais em ocorrências de violência doméstica: recomendações a partir de um estudo da Naturalistic Decision Making (ADMPG Journal, 2025)
Public security organizations play a fundamental role in combating violence against women and girls, a current and relevant issue for Brazilian society, given the increase in indicators associated with the issue. In order to contribute to improving decision-making by police officers in this scenario, this article seeks to understand the macrocognitive processes of police officers during intervention in domestic violence incidents, using the Naturalistic Decision Making (NDM) approach. Data was collected and processed through cognitive task analysis, using the critical decision method. The results indicate similarities in the decision-making process of military police officers when dealing with emergency and post-traumatic domestic violence incidents, suggesting the construction of a common map of police officers' cognitive processes in various incident scenarios. The study's contributions include the observation that multiple training and life experiences are necessary for police officers who work in the context of domestic violence, and that organizational practices that promote the maintenance of a common basis of understanding and shared mental models favor success in the decision-making process in the context studie